Corn Starch/Soybean Wax Double Coated Biochar-based Controlled-release Nitrogen Fertilizer: Water Retention, Release Kinetics and Okra Growth - I. J. X. Yong; I. A. W. Tan; D. H. H. Sim; L. L. P. Lim (Water, Air, & Soil Pollution, 2026)

Pan‐Arctic Peatlands Have Expanded During Recent Warming - J. Handley; R. E. Fewster; T. G. Sim; S. Hodson; B. Parker; K. Crichton; D. Charman; K. Anderson; M. Garneau; M. Väliranta; D. W. Beilman; G. T. Swindles; et al. (Global Change Biology, 2026)
The fate of carbon stored in Arctic peatlands remains uncertain because of the complex nature of the effects of climate change on permafrost and peatland carbon cycling. Expansion and/or shrinkage of Arctic peatlands under climate change also remain unknown due to lack of ground data and difficulties detecting changes in the extent of these ecosystems, meaning that land surface model predictions currently inadequately quantify Arctic terrestrial carbon storage changes. Pan‐Arctic shifts in peatland extent would profoundly change the fate of carbon in the terrestrial Arctic. Here, we tackle this knowledge gap by answering three main questions: (a) has lateral expansion occurred in Arctic peatlands as a response to recent warming? (b) if so, how fast has this occurred? (c) how does the response vary regionally? To answer these, we collected a dataset (12 peatland sites, 91 peat cores) combining peat cores collected across two latitudinal (north–south) transects: one in the European Arctic and one in the Canadian Arctic. In each region, we selected three peatland sites, with cores collected from transects spanning the peat‐edge to the peat‐centre. Our large‐scale dataset shows that peatlands have expanded, often rapidly, with some rates exceeding ~1 m per year since 1950 AD. This rapid expansion has occurred during a period of widespread Arctic warming and is still ongoing: two thirds (8/12) of our peatland sites evidence new peat formation after ~1990 AD based on age‐depth models constrained by 14 C and 210 Pb dating. Given that our sites comprise a broad range of Arctic conditions, we expect peatland expansion to be a pan‐Arctic phenomenon. Within specific regions, there are constraints on peat expansion including topographical limits, but we present the basis for future work to estimate pan‐Arctic peatland expansion, plus the associated carbon cycle implications under future climate change.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Pelagic sharks target long‐lived, retentive anticyclonic eddies in the Northwest Atlantic Ocean - Camrin D. Braun; Peter Gaube; Alice Della Penna; Simon R. Thorrold; Laura H. McDonnell; G. Chris Fischer; Gonzalo Mucientes; Nuno Queiroz; Mahmood Shivji; David W. Sims; Gregory B. Skomal; Bradley Wetherbee; et al. (Limnology and Oceanography, 2025)
Open ocean ecosystems represent the largest habitat on Earth and are highly dynamic in time and space. Mesoscale eddies are a primary driver of this variability and serve a key structural role in ocean ecosystems. Eddies modulate marine biodiversity beyond their impacts on plankton, influencing many ecologically and commercially important predators that may preferentially occupy anticyclonic eddies. However, how animal‐eddy interactions scale across predator species and the mechanistic drivers of these relationships remain an area of active research. We integrated satellite tracking data for sharks with observations of mesoscale eddies to determine how four shark species interact with eddies in the Gulf Stream region. Based on over 24,000 tracking days, we found that blue, white, and shortfin mako sharks selected for the cores of anticyclones while the use of eddies by tiger sharks was less conspicuous. Some particularly large and long‐lived anticyclones were occupied by tagged sharks for multiple weeks suggesting that these eddies may serve as hotspots for pelagic predators.

Per- and polyfluoroalkyl substances (PFAS) in the rivers of the Western United States - D. B. Sims; J. R. Monk; D. Woldetsadik; A. C. Hudson; M. C. Garner; K. Lindley; J. Piacentini; A. C. Buch; C. Cohu; C. S. Duvall; J. Blaszczak; J. Krause; et al. (International Journal of Environmental Science and Technology, 2025)

A framework for optimising opportunistic collaborative syntheses to propel ecological conservation - Ana M.M. Sequeira; Amanda E. Bates; Graeme Hays; David W. Sims; Samantha Andrzejaczek; Asta Audzijonyte; Julia K. Baum; Martin Beal; Barbara Block; Joshua Cinner; Kaitlyn Cowley; Eric Gilman; et al. (Biological Conservation, 2024)

Global habitat predictions to inform spatiotemporal fisheries management: Initial steps within the framework - Heather D. Bowlby; Jean-Noël Druon; Jon Lopez; Maria José Juan-Jordá; María Teresa Carreón-Zapiain; Frederic Vandeperre; Agostino Leone; Brittany Finucci; Philippe S. Sabarros; Barbara A. Block; Haritz Arrizabalaga; Pedro Afonso; et al. (Marine Policy, 2024)

Context-dependent changes in maritime traffic activity during the first year of the COVID-19 pandemic - Alexandra Loveridge; Christopher D. Elvidge; David A. Kroodsma; Timothy D. White; Karen Evans; Akiko Kato; Yan Ropert-Coudert; Julia Sommerfeld; Akinori Takahashi; Robert Patchett; Benjamin Robira; Christian Rutz; et al. (Global Environmental Change, 2024)

The dynamic influence of subsurface geological processes on the assembly and diversification of thermophilic microbial communities in continental hydrothermal systems - Kenneth W.W. Sims; Cole M. Messa; Sean R. Scott; Andrew D. Parsekian; Andrew Miller; Abraham L. Role; Timothy P. Moloney; Everett L. Shock; Jacob B. Lowenstern; R. Blaine McCleskey; Matthew A. Charette; Bradley J. Carr; et al. (Geochimica et Cosmochimica Acta, 2023)

Coral assemblages at higher latitudes favor short‐term potential over long‐term performance - James Cant; James D. Reimer; Brigitte Sommer; Katie M. Cook; Sun W. Kim; Carrie A. Sims; Takuma Mezaki; Cliodhna O'Flaherty; Maxime Brooks; Hamish A. Malcolm; John M. Pandolfi; Roberto Salguero‐Gómez; et al. (Ecology, 2023)
The persistent exposure of coral assemblages to more variable abiotic regimes is assumed to augment their resilience to future climatic variability. Yet, while the determinants of coral population resilience across species remain unknown, we are unable to predict the winners and losers across reef ecosystems exposed to increasingly variable conditions. Using annual surveys of 3171 coral individuals across Australia and Japan (2016–2019), we explore spatial variation across the short‐ and long‐term dynamics of competitive, stress‐tolerant, and weedy assemblages to evaluate how abiotic variability mediates the structural composition of coral assemblages. We illustrate how, by promoting short‐term potential over long‐term performance, coral assemblages can reduce their vulnerability to stochastic environments. However, compared to stress‐tolerant, and weedy assemblages, competitive coral taxa display a reduced capacity for elevating their short‐term potential. Accordingly, future climatic shifts threaten the structural complexity of coral assemblages in variable environments, emulating the degradation expected across global tropical reefs.

Nitrate: The Dr. Jekyll and Mr. Hyde of human health? - Catherine P. Bondonno; Liezhou Zhong; Nicola P. Bondonno; Marc Sim; Lauren C. Blekkenhorst; Alex Liu; Anjana Rajendra; Pratik Pokharel; Dorit W. Erichsen; Oliver Neubauer; Kevin D. Croft; Jonathan M. Hodgson (Trends in Food Science & Technology, 2023)

Circles in the sea: annual courtship “torus” behaviour of basking sharks Cetorhinus maximus identified in the eastern North Atlantic Ocean - David W. Sims; Simon D. Berrow; Ken M. O'Sullivan; Nicholas J. Pfeiffer; Richard Collins; Kev L. Smith; Brianna M. Pfeiffer; Paul Connery; Shane Wasik; Lois Flounders; Nuno Queiroz; Nicolas E. Humphries; et al. (Journal of Fish Biology, 2022)
Groups of basking sharks engaged in circling behaviour are rarely observed, and their function remains enigmatic in the absence of detailed observations. Here, underwater and aerial video recordings of multiple circling groups of basking sharks during late summer (August and September 2016–2021) in the eastern North Atlantic Ocean showed groups numbering between 6 and 23 non‐feeding individuals of both sexes. Sharks swam slowly in a rotating “torus” (diameter range: 17–39 m), with individuals layered vertically from the surface to a maximum depth of 16 m. Within a torus, sharks engaged in close‐following, echelon, close‐flank approach or parallel‐swimming behaviours. Measured shark total body lengths were 5.4–9.5 m (mean L T : 7.3 m ± 0.9 s.d. ; median: 7.2 m, n = 27), overlapping known lengths of sexually mature males and females. Males possessed large claspers with abrasions that were also observed on female pectoral fins. Female body colouration was paler than that of males, similar to colour changes observed during courtship and mating in other shark species. Individuals associated with most other members rapidly (within minutes), indicating toroidal behaviours facilitate multiple interactions. Sharks interacted through fin–fin and fin–body contacts, rolling to expose the ventral surfaces to following sharks, and breaching behaviour. Toruses formed in late summer when feeding aggregations in zooplankton‐rich thermal fronts switched to non‐feeding following and circling behaviours. Collectively, the observations explain a courtship function for toruses. This study highlights northeast Atlantic coastal waters as a critical habitat supporting courtship reproductive behaviour of endangered basking sharks, the first such habitat identified for this species globally.

Extinct groundwater discharge locality in the Eldorado Valley; eastern Mojave Desert, Nevada, USA - Douglas B. Sims; Amanda C. Hudson; John E. Keller; Paul McBurnett; David Ferrari; Giavanna M. Fernandez; Juan Garcia-Hernandez; Bailey D. Kesl; Flavio W. Rodriguez; Sean G. Torres (Journal of Sedimentary Environments, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Tropical macrophytes promote phytoplankton community shifts in lake mesocosms: relevance for lake restoration in warm climates - Darren Z. H. Sim; Maxine A. D. Mowe; Yiluan Song; Joy Lu; Hugh T. W. Tan; Simon M. Mitrovic; Daniel L. Roelke; Darren C. J. Yeo (Hydrobiologia, 2021)

Kappa opioid receptors mediate an initial aversive component of paclitaxel-induced neuropathy - Julie A. Meade; Y. Alkhlaif; K. M. Contreras; S. Obeng; W. Toma; L. J. Sim-Selley; D. E. Selley; M. I. Damaj (Psychopharmacology, 2020)

Refugia under threat: Mass bleaching of coral assemblages in high‐latitude eastern Australia - Sun W. Kim; Eugenia M. Sampayo; Brigitte Sommer; Carrie A. Sims; Maria del C. Gómez‐Cabrera; Steve J. Dalton; Maria Beger; Hamish A. Malcolm; Renata Ferrari; Nicola Fraser; Will F. Figueira; Stephen D. A. Smith; et al. (Global Change Biology, 2019)
Environmental anomalies that trigger adverse physiological responses and mortality are occurring with increasing frequency due to climate change. At species' range peripheries, environmental anomalies are particularly concerning because species often exist at their environmental tolerance limits and may not be able to migrate to escape unfavourable conditions. Here, we investigated the bleaching response and mortality of 14 coral genera across high‐latitude eastern Australia during a global heat stress event in 2016. We evaluated whether the severity of assemblage‐scale and genus‐level bleaching responses was associated with cumulative heat stress and/or local environmental history, including long‐term mean temperatures during the hottest month of each year (SST LTMAX ), and annual fluctuations in water temperature (SST VAR ) and solar irradiance (PARZ VAR ). The most severely‐bleached genera included species that were either endemic to the region ( Pocillopora aliciae ) or rare in the tropics (e.g. Porites heronensis ). Pocillopora spp., in particular, showed high rates of immediate mortality. Bleaching severity of Pocillopora was high where SST LTMAX was low or PARZ VAR was high, whereas bleaching severity of Porites was directly associated with cumulative heat stress. While many tropical Acropora species are extremely vulnerable to bleaching, the Acropora species common at high latitudes, such as A. glauca and A. solitaryensis , showed little incidence of bleaching and immediate mortality. Two other regionally‐abundant genera, Goniastrea and Turbinaria , were also largely unaffected by the thermal anomaly. The severity of assemblage‐scale bleaching responses was poorly explained by the environmental parameters we examined. Instead, the severity of assemblage‐scale bleaching was associated with local differences in species abundance and taxon‐specific bleaching responses. The marked taxonomic disparity in bleaching severity, coupled with high mortality of high‐latitude endemics, point to climate‐driven simplification of assemblage structures and progressive homogenisation of reef functions at these high‐latitude locations.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

The use of historical environmental monitoring data to test predictions on cross-scale ecological responses to alterations in river flows - Matthew J. Colloff; Ian C. Overton; Brent L. Henderson; Jane Roberts; Julian R. W. Reid; Roderick L. Oliver; Anthony D. Arthur; Tanya M. Doody; Neil C. Sims; Qifeng Ye; Susan M. Cuddy (Aquatic Ecology, 2018)

Shallow-level differentiation of phonolitic lavas from Sumaco Volcano, Ecuador - Jennifer M. Garrison; Kenneth W. W. Sims; Gene M. Yogodzinski; Ricardo D. Escobar; Sean Scott; Patricia Mothes; Minard L. Hall; Patricio Ramon (Contributions to Mineralogy and Petrology, 2018)

To Madagascar and back: long‐distance, return migration across open ocean by a pregnant female bull shark Carcharhinus leucas - J. S. E. Lea; N. E. Humphries; C. R. Clarke; D. W. Sims (Journal of Fish Biology, 2015)
A large, pregnant, female bull shark Carcharhinus leucas was tracked migrating from Seychelles across open ocean to south‐east Madagascar, c. 2000 km away, and back again. In Madagascar, the shark spent a prolonged period shallower than 5 m, consistent with entering estuarine habitat to pup, and upon return to Seychelles the shark was slender and no longer gravid. This represents an unprecedented return migration across the open ocean for a C. leucas and highlights the need for international collaboration to manage the regional C. leucas population sustainably.

The biology, ecology and conservation of elasmobranchs: recent advances and new frontiers - D. W. Sims (Journal of Fish Biology, 2015)

Proof-of-concept randomized controlled trial of pregnenolone in schizophrenia - Christine E. Marx; Jimmy Lee; Mythily Subramaniam; Attilio Rapisarda; Dianne C. T. Bautista; Edwin Chan; Jason D. Kilts; Robert W. Buchanan; Eu Pui Wai; Swapna Verma; Kang Sim; Jayaraman Hariram; et al. (Psychopharmacology, 2014)

Inferred global connectivity of whale shark Rhincodon typus populations - A. M. M. Sequeira; C. Mellin; M. G. Meekan; D. W. Sims; C. J. A. Bradshaw (Journal of Fish Biology, 2013)
Ten years have passed since the last synopsis of whale shark Rhincodon typus biogeography. While a recent review of the species' biology and ecology summarized the vast data collected since then, it is clear that information on population geographic connectivity, migration and demography of R. typus is still limited and scattered. Understanding R. typus migratory behaviour is central to its conservation management considering the genetic evidence suggesting local aggregations are connected at the generational scale over entire ocean basins. By collating available data on sightings, tracked movements and distribution information, this review provides evidence for the hypothesis of broad‐scale connectivity among populations, and generates a model describing how the world's R. typus are part of a single, global meta‐population. Rhincodon typus occurrence timings and distribution patterns make possible a connection between several aggregation sites in the Indian Ocean. The present conceptual model and validating data lend support to the hypothesis that R. typus are able to move among the three largest ocean basins with a minimum total travelling time of around 2–4 years. The model provides a worldwide perspective of possible R. typus migration routes, and suggests a modified focus for additional research to test its predictions. The framework can be used to trim the hypotheses for R. typus movements and aggregation timings, thereby isolating possible mating and breeding areas that are currently unknown. This will assist endeavours to predict the longer‐term response of the species to ocean warming and changing patterns of human‐induced mortality.

Identifying reproductive events using archival tags: egg‐laying behaviour of the small spotted catshark Scyliorhinus canicula - V. J. Wearmouth; E. J. Southall; D. Morritt; D. W. Sims (Journal of Fish Biology, 2013)
The use of archival depth telemetry as a means of remotely assessing the reproductive rates of free‐ranging fishes is explored. This is achieved by electronically tracking the vertical movements of individual female small spotted catsharks Scyliorhinus canicula in the natural environment, whilst simultaneously evaluating the temporal and vertical distributions of egg‐laying in this species. Distinctive patterns of short‐term (0·3–3·7 h), shallow‐water activity are documented in the time–depth profiles of female S. canicula that occur at an appropriate depth (1·0–2·3 m) and periodicity (every 10–12 days) to represent egg‐laying behaviour. Putative egg‐laying behaviour was exhibited simultaneously by two individually tracked female S. canicula during late‐spring and early‐summer. The results highlight that, provided species behaviour is suitable and complementary methods such as previous data, laboratory experiments and field surveys can be used to validate the patterns observed, archival depth telemetry offers an unobtrusive means by which egg production and egg‐laying behaviour of free‐living fishes can be estimated. As precise information regarding life‐history parameters is difficult to obtain for free‐ranging fish species, this technique could be used to improve the parameterization of species demographic models that are relevant to the management of wild fish populations.

The effect of familiarity on aggregation and social behaviour in juvenile small spotted catsharks Scyliorhinus canicula - D. M. P. Jacoby; D. W. Sims; D. P. Croft (Journal of Fish Biology, 2012)
This study was designed to address whether juvenile small spotted catsharks Scyliorhinus canicula aggregate and to determine whether potential aggregation is underpinned by social preferences for conspecifics. Using controlled and replicated experiments, the role of familiarity as a potential mechanism driving aggregation and social behaviour in this species was considered. Observed S. canicula association data compared to null model simulations of random distributions revealed differences in aggregation under different social contexts. Only familiar juvenile S. canicula aggregated more than would be expected from random distribution across their habitat. Familiarity increased the mean number of groups but did not significantly affect mean group size. Significant preference and avoidance behaviour across all groups were also observed. Furthermore, the strength of social attraction, quantified by the mean association index, was significantly higher in groups containing familiar individuals. Mixed familiar and unfamiliar treatments were also conducted to test for within‐ and between‐group effects, finding high variation across replicates with some groups assorting by familiarity and others not. It is believed that this study is the first to examine experimentally the influence of conspecific familiarity on aggregation behaviour in sharks. These results not only imply a functional benefit to aggregation, but also suggest that persistent social affiliation is likely to influence dispersal following hatching in this small benthic elasmobranch.

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

The biology and ecology of the ocean sunfish Mola mola: a review of current knowledge and future research perspectives - Edward C. Pope; Graeme C. Hays; Tierney M. Thys; Thomas K. Doyle; David W. Sims; Nuno Queiroz; Victoria J. Hobson; Lukas Kubicek; Jonathan D. R. Houghton (Reviews in Fish Biology and Fisheries, 2010)

Oceans apart? Short‐term movements and behaviour of adult bull sharks Carcharhinus leucas in Atlantic and Pacific Oceans determined from pop‐off satellite archival tagging - J. M. Brunnschweiler; N. Queiroz; D. W. Sims (Journal of Fish Biology, 2010)
Adult bull sharks Carcharhinus leucas were monitored with electronic tags to investigate horizontal and vertical movements in the Atlantic and Pacific Oceans. In both locations, C. leucas showed some fidelity to specific coastal areas with only limited horizontal movements away from the tagging sites after tag attachment. Fish tagged in the Bahamas were detected mostly in the upper 20 m of the water column in water 25–26° C, whereas C. leucas tagged in Fiji spent most of their time below 20 m in water usually >26° C. The results highlight the importance of coastal inshore habitats for this species.

Deep‐diving behaviour of a whale shark Rhincodon typus during long‐distance movement in the western Indian Ocean - J. M. Brunnschweiler; H. Baensch; S. J. Pierce; D. W. Sims (Journal of Fish Biology, 2009)
A whale shark Rhincodon typus satellite tagged off the coast of Mozambique showed a highly directional movement across the Mozambique Channel and around the southern tip of Madagascar, a minimum distance of 1200 km in 87 days. Dives to depths well into the mesopelagic and bathypelagic zones (1286 m maximum depth) were recorded in a bathymetrically non‐constraining habitat. The water temperature range recorded during the fish’s movement was 3·4–29·9° C.

Effects of environment on electric field detection by small spotted catshark Scyliorhinus canicula (L.) - J. L. Filer; C. G. Booker; D. W. Sims (Journal of Fish Biology, 2008)
This study evaluated the influence of environment (substratum type and depth) on the electroreception capabilities of small spotted catsharks Scyliorhinus canicula in response to prey‐simulating electric fields. In experiments where electric fields (applied current 15 μA) were presented beneath different substrata (sand, pebbles, rocks and control) it was found that search effort was not different between substrata or S. canicula sexes, however, both rates of turning and biting towards active electrodes were decreased over pebbles and rocks compared with sand and the control (no substratum). There was no significant effect of sex on turn and bite rates over any substrata. Electric fields were then presented beneath different depths of sand to examine the depth‐limits of fish electroreception. Turn and bite rates were significantly lower at depths below 10 mm, with no bites towards electrodes made when they were >30 mm depth. Search effort was not found to be different between different burial depth treatments or between sexes. These results indicate substratum type and depth influences the ability of S. canicula to detect prey‐simulating electric fields. This variation in electroreceptive performance may influence space use of sharks.

Sex differences in dogfish behaviour: alternative activity patterns and habitat choice - V. J. Wearmouth; D. W. Sims; J. C. Partridge; I. C. Cuthill (Journal of Fish Biology, 2003)
Acoustic tracking of wild lesser spotted dogfish, Scyliorhinus canicula , in Lough Hyne, a tidal sea‐water lough in southwest Ireland, has demonstrated that the sexes exhibit alternative behaviours. Male dogfish remain active throughout the day and night in deep water (12–24 m), and forage in shallow or deep water by night. Female dogfish, on the other hand, refuge in shallow water caves by day (

Tractable models for testing theories about natural strategies: foraging behaviour and habitat selection of free‐ranging sharks - D. W. Sims (Journal of Fish Biology, 2003)
Marine and terrestrial environments differ fundamentally in space‐time scales of both physical and ecological processes. These differences will have an impact on the animals inhabiting each domain, particularly with respect to their spatial ecology. The behavioural strategies that underpin observed distributions of marine species are therefore important to consider. Comparatively little is known, however, about how wild fishes actually respond to gradients in food supply and temperature, and to potential mates. This paper describes how behavioural theory is being used to elucidate the strategies and tactics of free‐ranging sharks in three specific areas of study, namely, foraging on zooplankton, behavioural energetics and sexual segregation. The studies discussed are novel because shark movements were tracked in the wild using electronic tags in relation to simultaneous measurements of prey densities and thermal resources. The results show that filter‐feeding (basking shark, Cetorhinus maximus ) and predatory (dogfish, Scyliorhinus canicula ) sharks have relatively complex behaviour patterns integrally linked to maximizing surplus power, often through making short and longer term ‘trade‐off’ decisions between optimal foraging and thermal habitats. Interestingly, female S. canicula exhibit alternative behavioural strategies compared to males, a difference resulting in spatial segregation by habitat. Sexual segregation in this species occurs primarily as a consequence of male avoidance by females. Studies on free‐ranging sharks provide a useful model system for examining how a predator's strategy is shaped by its environment. More theory‐based studies of the behavioural processes of sharks are required however, before critical comparisons with other vertebrate predators are possible. Suggestions for further research to address this knowledge gap are given.

Virus Isolation for Diagnosing Dengue Virus Infections in Returning Travelers - D. Teichmann; K. Gbels; M. Niedrig; J.-W. Sim-Brandenburg; J. Lge-Stehr; M. P. Grobusch (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Comparison of the Effects of Wet N Deposition (NH4Cl) and Dry N Deposition (NH3) on UK Moorland Species - Ian D. Leith; Lucy J. Sheppard; Carole E.R. Pitcairn; J. Neil Cape; Paul W. Hill; Valerie H. Kennedy; Y. Sim Tang; Ron I. Smith; David Fowler (Water, Air, & Soil Pollution, 2001)

Basking shark occurrence off south‐west England in relation to zooplankton abundance - D. W. Sims; A. M. Fox; D. A. Merrett (Journal of Fish Biology, 1997)
Basking sharks Cetorhinus maximus >3 m total length arrived off Plymouth, U.K. directly after the increase in zooplankton density in May, while young‐of‐the‐year basking sharks ( −3 ). No basking sharks were seen after July when the zooplankton density was least.

Mapping the bovine factor H gene to Chromosome 16 by SSCP analysis - J. L. Williams; D. H. Lester; V. M. Teres; W. Barendse; R. B. Sim; C. J. Soames (Mammalian Genome, 1997)